ENGLISH TEACHERS' BELIEFS AND PRACTICES IN COMMUNICATIVE LANGUAGE TEACHING :A Case Study of English Teachers at an MTsN in Jambi - Pajarwaty, Desy (2009)
This study, drawing on the ideas associated with teachers' beliefs, aims to suggest that we should explore teachers' instructional practice and provides insight to examine how English teachers make instructional decisions, choose instructional materials, and select certain instructional practice in applying communicative language teaching (CLT). This approach has been socialized and applied for years at least since 1984 English curriculum. There was enough time for English teachers to be familiar with the teaching of English using CLT both in theory and practice. However, it seems that the CLT has not been applied optimally yet in class. Being difficult for Islamic Junior High School students to communicate in English indicated that the teaching of English with CLT based curriculum did not make any meaningful or distinctive progress for the students' communicative competence nor linguistic competence. For this, it was considered necessary to find out the teacher's beliefs about CLT and how it was implemented in classroom. This study applied qualitative case study method. Data were collected through questionnaire with five continuum of scale for the former, semi-structure interviews with three English teachers in Islamic Junior High School in Jambi and direct observations completed with observation checklist for the later. Result indicated that the teachers' beliefs, which came from their own language learning experience, teaching experience and expectation from the school inform their instructional practice in CLT tend to be strong, especially regarding to group work or pair work and student role. Whereas the implementation in classroom teaching in general is inconsistent since teachers brought their own model of teaching. Based on the findings, teachers should get more chances to be involved in in-service training focusing on putting the theory into practice to make them familiar with applying CLT principles in their classroom teaching. In addition to the government effort in providing teaching media, teachers should be creative in preparing their teaching suitable with the purpose and the context of the lesson being taught to the students by using authentic materials and the real object, as well as do self-reflection to improve their professional instruction.